Situating Zimbabwe's natural resource governance systems in history - Mandondo, A. (2000)
This paper reviews natural resource governance in Zimbabwe’s peasant sector from colonial to post-colonial times. Governance is considered within the framework of power, process and practice and how these shaped peasant access, control and use of natural resources. Colonial natural resource governance systems resulted in over-centralisation because they were crafted in the context of conquest and subjugation. Over the years, state visions of appropriate management and use of resources have largely been extended to the African peasant sector through a centrally-directed structure and process. However, state control over the use and management of resources among the peasantry was and is largely ineffectual because the state lacks the resources and capacity to enforce such controls. Much of the colonial legislation was inherited piecemeal into post-colonial times, and amendments to date have largely deracialised the colonial acts and policies without democratising them. Pioneering efforts at decentralizing entrustments over use and management of resources to the peasant communities have largely resulted in recentralisation at the district level, where such efforts are still practiced in the trickle-down mode. This is in part because the policy thrust seeking to empower the peasant communities is supply-led, and thus defined according to the terms and processes of external agents, including funders and central governments and their functionaries. The study argues that supply-led decentralisation needs to be complemented by demand-driven decentralisation.